Development of a simple high-throughput screening protocol based on biosynthetic activity of Mycobacterium tuberculosis glutamine synthetase for the identification of novel inhibitors - Singh, Upasana; Sarkar, Dhiman (Journal of Biomolecular Screening, 2006)
A high-throughput screening protocol has been developed for Mycobacterium tuberculosis glutamine synthetase by quantitative estimation of inorganic phosphate. The K., values determined at pH 6.8 are 22 mM for L-glutamic acid, 0.75 mM for NH4Cl, 3.25 mM for MgCl2, and 2.5 mM for adenosine triphosphate. The K-m value for glutamine is affected significantly by the increase in pH of assay buffer. At the saturating level of the substrate, the enzyme activity at pH 6.8 and 25 degrees C is found to be linear up to 3 h. The reduction of enzyme activity is negligible even in presence of 10% DMSO. The Z' factor and signal-to-noise ratio are found to be 0.75 and 6.18, respectively, when the enzyme is used at 62.5 mu g/ml concentration. The IC50 values obtained at pH 6.8 for both L-methionine S-sulfoximine and DL-phosphothriacin are 500 mu M and 30 pM, respectively, which is lowest compared to the values obtained at other pH levels. The Beckman Coulter high-throughput screening platform was found to take 5 h 9 min to complete the screening of 60 plates. For each assay plate, a replica plate is used to normalize the data. Screening of 1164 natural product fractions/extracts and synthetic molecules from an in-house library was able to identify 12 samples as confirmed hits. Altogether, the validation data from screening of a small set of an in-house library coupled with Z' and signal-to-noise values indicate that the protocol is robust for high-throughput screening of a diverse chemical library.
Keywords: Beckman Coulter; biosynthetic activity; Glutamine synthetase; high-throughput screening; Mycobacterium tuberculosis

Novel screening method based on menadione mediated rapid reduction of tetrazolium salt for testing of anti-mycobacterial agents - Singh, Upasana; Akhtar, Shamim; Mishra, Abhishek; Sarkar, Dhiman (Journal of Microbiological Methods, 2011)
A microplate-based rapid, inexpensive and robust technique is developed by using tetrazolium salt 2, 3-bis [2-methyloxy-4-nitro-5-sulfophenyl]-2H-tetrazolium-5-carboxanilide (XTT) and menadione to determine the viability of Mycobacterium tuberculosis, Mycobacterium bovis BCG and Mycobacterium smegmatis bacilli in microplate format. In general, XTT reduction is an extremely slow process which takes almost 24 h to produce a detectable signal. Menadione could drastically induce this reduction to an almost equal extent within a few minutes in a dose dependent manner. The reduction of XTT is directly proportional to the cell concentration in the presence of menadione. The standardized protocol used 200 mu M of XTT and 60 mu M of menadione in 250 mu l of cell suspension grown either in aerobic or anaerobic conditions. The cell suspension of M. bovis BCG and M. tuberculosis were incubated for 40 min before reading the optical density at 470 nm whereas M. smegmatis was incubated for 20 min. Calculated Signal/Noise (S/N) ratios obtained by applying this protocol were 5.4, 6.4 and 9.4 using M. bovis BCG. M. tuberculosis and M. smegmatis respectively. The calculated Z' factors were > 0.8 for all mycobacterium bacilli indicating the robustness of the XTT Reduction Menadione Assay (XRMA) for rapid screening of inhibitors. The assay protocol was validated by applying 10 standard anti-tubercular agents on M. tuberculosis, M. bovis BCG and M. smegmatis. The Minimum Inhibitory Concentration (MIC) values were found to be similar to reported values from Colony Forming Unit (CFU) and REMA (resazurin microplate assay) assays. Altogether. XRMA is providing a novel anti-tubercular screening protocol which could be useful in high throughput screening programs against different physiological stages of the bacilli. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Menadione; Mycobacterium tuberculosis; Tetrazolium salt; XRMA

Advanced cell-based high-throughput screening assays targeting active and latent Mycobacterium tuberculosis - Shurpali, Ketaki Dilip; Singh, Upasana; Sarkar, Shamim Akhtar Sampa; Mishra, Abhishek; Kulkarni, Roshan; Joshi, Swati P.; Sarkar, Dhiman (Journal of Biotechnology, 2014)
European Biotechnology Congress, Lecce, ITALY, MAY 15-18, 2014